Creatine or guanidinoacetic acid? Which is more effective at enhancing growth, tissue creatine stores, quality of meat, and genes controlling growth/myogenesis in Mulard ducks - Doaa Ibrahim; Rania El Sayed; Ahmed Abdelfattah-Hassan; A. M. Morshedy (Journal of Applied Animal Research, 2019)
This study aimed to determine the effectiveness of guanidinoacetic acid (GAA) with or without methionine (Met) compared to creatine (CREA) at enhancing duck’s performance, restoring tissue CREA and improving meat quality. Mulard ducklings (n = 250) were randomly assigned to control (without additives), or control plus CREA, GAA, GAA + 0.2%Met (GAAMet0.2) or GAA + 0.4%Met (GAAMet0.4) groups in a completely random experimental design. Dietary supplementation of CREA or GAA significantly increased (P < 0.05) overall weight gain and improved feed:gain ratio. Supplementation of GAA (especially GAAMet0.4 group) significantly increased (P < 0.05) carcass and breast yield. Meat pH values were higher (P < 0.05) with dietary GAA + Met or CREA. Providing of dietary GAA + Met led to higher levels of plasma CREA than dietary CREA itself. The molecular investigation indicated that dietary CREA or GAA with Met enhanced the gene expression of hepatic insulin-like growth factor-1, growth hormone and muscle myogenin. Finally, dietary GAA + Met was superior to CREA in improving duck’s performance based on molecular markers related to growth (IGF-1 and growth hormone) and myogenesis (upregulating myogenin and downregulating myostatin). Although, dietary GAA + Met enhanced muscle’s CREA loading than CREA, the long-term GAA supplementation in ducks may induce methyl-groups shortage for protein synthesis, this was resolved with Met addition in our study.